Sorcellerie en milieu urbain amplifiée par les pentecôtismes camerounais - Batibonak, Sariette (Afrika Focus, 2012)
Once considered as a "rural" phenomenon, issues pertaining to the occult have, at the height of globalization, become an "urban" problem. Witchcraft is particularly invoked to designate suc- cess; to provide information on individual and collective misfortunes, justifying battles against fetishes, misfortune, bad genies and all kinds of evil spirits leading to poverty, unemployment, bad luck or (a state of ) being possessed. Increasingly since the nineties, the city has become the stage for Pentecostal effervescence. Preacher-healers have settled predominately in urban areas and play a crucial role in the reconstruction of sorcery's collective imagery, updating magical- religious systems of reference; rehabilitating exorcism and devotion in matters of deliverance. Religious and magical justi cations have become regular features of urban acts and behaviours. In this context, witchcraft distinguishes itself as a response to urban life and could even be one of its founding elements. What are its urban markers? How does it express itself in contemporary urban life? Using an in situ approach, active observation and semi-structured interviews – this research examines, from an ethnographical perspective, urban witchcraft as ampli ed by a Pente- costal discourse vector of anti-witchcraft violence. Key words: witchcraft, Pentecostalism, urban, occultism, churches